Roles of Neuropeptides, VIP and AVP, in the Mammalian Central Circadian Clock - Ono, Daisuke; Honma, Ken-ichi; Honma, Sato (Frontiers in Neuroscience, 2021)
In mammals, the central circadian clock is located in the suprachiasmatic nucleus (SCN) of the hypothalamus. Individual SCN cells exhibit intrinsic oscillations, and their circadian period and robustness are different cell by cell in the absence of cellular coupling, indicating that cellular coupling is important for coherent circadian rhythms in the SCN. Several neuropeptides such as arginine vasopressin (AVP) and vasoactive intestinal polypeptide (VIP) are expressed in the SCN, where these neuropeptides function as synchronizers and are important for entrainment to environmental light and for determining the circadian period. These neuropeptides are also related to developmental changes of circadian system of the SCN. Transcription factors are required for the formation of neuropeptide-related neuronal networks. Although VIP is critical for synchrony of circadian rhythms in the neonatal SCN, it is not required for synchrony in the embryonic SCN. During postnatal development, the clock gene cryptochrome1 and 2 are involved in the maturation of cellular networks, and AVP is involved in SCN networks. This mini-review focuses on the functional roles of neuropeptides in the SCN based on recent findings in the literature.